Investigating the Influence of Social Media on Youth Engagement in the August 2024 #EndBadGovernance Protests in Nigeria - Bassey, Andrew Ubong (Technium Social Sciences Journal, 2024)
Social media has emerged as a significant platform for political, economic, and social dialogue worldwide, acting as a vehicle for self-expression and a means to hold political leaders accountable. In Nigeria, platforms such as Facebook, X, WhatsApp, and Instagram have played a crucial role in the organisation and mobilisation of protests. This study explores the impact of social media on youth participation in the August 2024 #EndBadGovernance protests in Nigeria. Using the public sphere theory, the research adopted a quantitative survey approach, collecting data from 300 respondents across the six Area Councils of the Federal Capital Territory, Abuja. The results reveal that social media was instrumental in mobilising and engaging young people during the protests. Prominent themes discussed on social media included the high cost of living, reversal of the fuel subsidy removal, investigation of the fuel subsidy regime, reduction in electricity tariffs, high cost of governance, corruption, deficiencies in educational and healthcare systems, unemployment, insecurity, and widespread poverty. This study highlights social media's dual function as both a catalyst for mobilisation and a tool for organisational coordination. It is recommended that public training on the responsible use of social media be implemented to maximise its effectiveness in civic engagement.